Benefits and Challenges of Using NodeJS - Basumatary, Bonjar; Agnihotri, Nishant (International Journal of Innovative Research in Computer Science & Technology, 2022)
Node.js, the JavaScript runtime environment is very popular among Full Stack Developers for building Web applications. It gives the developer to write server-side code in JavaScript and able to manage both client and server side. Node.js ensures outstanding performance, it applies event-driven, non-blocking input output and asynchronous paradigm. The study is based on benefits and challenges of using Node.js. The results of study are from comparing different web development programming languages with JavaScript which is used in Node.js. And in the end some suggestions on how to improve those areas and make it more feasible.